Technoliteracy, discourse, and social practice : frameworks and applications in the digital age - Baguley, Margaret, 1966-; Gitsaki, Christina; Pullen, Darren L. (Information Science Reference, 2010)
"This book provides a unique and important insight into the diverse approaches to, and implementation of, technoliteracy in different contexts, presenting the significance and value of preparing students, educators and those responsible for information technology to use IT effectively and ethically to enhance learning"--Provided by publisher